No Italian Stalingrads. The C.G.I.L. and the working class in the northern industrial heartlands, 1945-1955. Issue 5 (20th October 2018) - De Graaf, Jan
ABSTRACT: This article challenges conventional wisdom on the northern Italian industrial heartlands during the first decade after the Second World War. For there still exists a certain mythology about the post-war proletarian north as a region that was both intensely political and united in purpose. What this article demonstrates is that the 'industrial triangle' of Genoa, Milan and Turin was far more divided than historians have assumed. By revisiting the manifold (wildcat) strikes, trade union demonstrations, and factory occupations of the early post-war years, it shows the industrial north to be divided along both social and geographical lines. In doing so, it sheds fresh light on the series of defeats that the main Italian trade union confederation (C.G.I.L.) suffered in the late 1940s and early 1950s. It argues that these defeats were due as much to the explicit politicization of labour struggles and their exclusive focus on the interests of skilled workers as to the hostile socio-political climate in which the C.G.I.L. had to operate.